Os principais desconfortos físicos dos flautistas e suas implicações no estudo e na performance da flauta - Marcelo Parizzi Marques Fonseca (2005)
The lack of corporal consciousness and the consequent postural problems are liable to cause physical discomfort and difficultate both practice and flute performance. This research intends to investigate the incidence of physical discomfort among the flutists and the repercussions of these disconforts in their daily practice. As theoretical framework, we made a study of postural biomechanic and came to aconcept of healthy porture. Then, a transposition of these subjects was made to the flute practice and performance. The methodology, which assumed an exploratory approach, aimed to raise, through a structured questionary, the main physical discomforts among the flutists and the reflections of these discomforts in their daily lives. We hope this research will contribute to make flutists aware of the importance of corporal consciousness during their daily practice, in order to lengthen their activelife as musicians. Thinking about the most common physical discomforts among the flutists will also stimulate further studies about this subject, yet quite unknown among musicians.